STRATEGI KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU AKADEMIK BERBASIS PROGRAM KHUSUS DI SMP MUHAMMADIYAH - Khoiri Yahya Afifah; Zaenal Abidin; Darsinah; Wafrotur Rohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the principal's instructional leadership strategy in improving academic quality in schools based on special programs. This study used a qualitative approach with a case study method at SMP Muhammadiyah Program Khusus. Data were collected through in-depth interviews, participant observation, and documentation studies. The results showed that the instructional leadership strategy was carried out through three main pillars: (1) formulating a specific academic mission and vision by setting special program achievement indicators; (2) implementing academic supervision based on clinical mentoring to improve teachers' pedagogical competence; and (3) creating a conducive learning climate through the integration of technology and a culture of achievement. These findings indicate that the success of improving academic quality highly depends on the principal's ability to synergize national curriculum standards with the school's flagship programs. This research provides a theoretical contribution to instructional leadership models in faith-based private schools.